Praxisleitfaden Organspende Umsetzung der BÄK-Richtlinie "Spendererkennung" in der Praxis - Hahnenkamp, Klaus (MWV Medizinisch Wissenschaftliche Verlagsgesellschaft mbH & Co. KG, 2021)
The Organ Donation Practice Guide is based on the structure and content of the donor identification guidelines of the German Medical Association. The core element of the guideline is that doctors working in intensive care medicine in hospitals must enable organ donation from potential organ donors if there is a fundamental wish to donate organs. The practical guide provides the relevant knowledge for recognizing potential organ donors and the procedure for this event, which is rather rare in complex everyday clinical practice. The donation process is also fundamentally discussed with regard to donor identification. The book is aimed at doctors in intensive care units, transplant officers and all health professionals who may be confronted with potential organ donors.